Effect of tissue perfusion on microwave ablation: experimental in vivo study in porcine kidneys - Sommer, Christof-Matthias; Koch, Vitali; Pap, Bence; Bellemann, Nadine; Holzschuh, Maria; Gehrig, Tobias; Shevchenko, Maxym; Arnegger, Florian U.; Nickel, Felix; Mogler, Carolin; Zelzer, Sascha; Meinzer, Hans-Peter; et al. (Journal of vascular and interventional radiology, 2011)
Purpose - To determine the effect of tissue perfusion on microwave ablation lesions in an experimental in vivo study in porcine kidneys. - Materials and Methods - Twelve kidneys of six pigs were studied. In each animal, two microwave ablations were created in one kidney without limitation of tissue perfusion (group 1). In the other kidney, two microwave ablations were performed with interruption of blood flow (group 2). All microwave ablations were performed with identical system parameters (eg, temperature control mode, ablation time of 80 s, and temperature of 110°C). The animals were euthanized 3 hours later. The kidneys were harvested and cut into 2-3-mm transverse slices. Microwave ablation zone dimensions (eg, length, width, and volume) and shape (eg, sphericity ratio) and corresponding variability were compared between groups. - Results - Microwave ablation areas were significantly longer (41.6 mm ± 4.0 vs 34.2 mm ± 5.9; P < .01) and wider (16.6 mm ± 1.2 vs 12.2 mm ± 2.1; P < .001) in group 2 than in group 1. Similarly, microwave ablation volume was significantly greater in group 2 compared with group 1 (6.7 cm3 ± 1.0 vs 3.3 cm3 ± 1.2; P < .001). Ablation area shapes were similar between groups (sphericity ratio, 2.57 ± 0.42 vs 2.39 ± 0.34). Ablation area variabilities were also comparable between groups (volume variance of 1.32 vs 0.93; sphericity ratio variance of 0.18 vs 0.11). - Conclusions - After interruption of blood flow, microwave ablation areas are significantly larger than those achieved without limitation of tissue perfusion. Microwave ablation area shape and variability were comparable between study groups.